Analisis Sikap Peduli Lingkungan Siswa di Salah Satu MAN pada Materi Pelestarian Lingkungan - Annisa Qodriyanti; Husnin Nahry Yarza; Irdalisa Irdalisa; Mega Elvianasti; Rosi Feirina Ritonga (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The students' lack of environmental care attitude at one of the MAN Jakarta which was observed through observations during the second internship. This study aims to describe the environmental care attitude of students and the factors that influence it. This research uses descriptive quantitative analysis method with sampling technique using a questionnaire distributed through Google form. The population used was all students of class XI and XII IPA MAN Jakarta and then used the Cluster Random Sampling method and obtained a sample of 94 students. The results of this study found that the students' environmental care attitude on environmental preservation material in class X was in the medium category. The influencing factors include factors of daily habits at home, factors of self-awareness to care for the environment, factors of knowledge that students have, and factors of seeing organizations engaged in the environment.